Delayed aneurysm rupture due to residual blood flow at the inflow zone of the intracranial paraclinoid internal carotid aneurysm treated with the Pipeline embolization device: Histopathological investigation. Issue 6 (December 2015) - Ikeda, Hiroyuki; Ishii, Akira; Kikuchi, Takayuki; Ando, Mitsushige; Chihara, Hideo; Arai, Daisuke; Hattori, Etsuko; Miyamoto, Susumu
Cerebral aneurysm rupture is a serious complication that can occur after flow diverter (FD) placement, but the underlying mechanisms remain unclear. We encountered a case in which direct stress on the aneurysm wall caused by residual blood flow at the inflow zone near the neck during the process of thrombosis after FD placement appeared associated with aneurysm rupture. The patient was a 67-year-old woman with progressive optic nerve compression symptoms caused by a large intracranial paraclinoid internal carotid aneurysm. The patient had undergone treatment with a Pipeline embolization device (PED) with satisfactory adherence between the PED and vessel wall. Surgery was completed without complications, and optic nerve compression symptoms improved immediately after treatment. Postoperative clinical course was satisfactory, but the patient suddenly died 34 days postoperatively. Autopsy confirmed the presence of subarachnoid hemorrhage caused by rupture of the internal carotid aneurysm that had been treated with PED. Although the majority of the aneurysm lumen including the outflow zone was thrombosed, a non-thrombosed area was observed at the inflow zone. Perforation was evident in the aneurysm wall at the inflow zone near the neck, and this particular area of aneurysm wall was not covered in thrombus. Macrophage infiltration was not seen on immunohistochemical studies of the aneurysm wall near the perforation. A hemodynamically unstable period during the process of complete thrombosis of the aneurysm lumen after FD placement may be suggested, and blood pressure management and appropriate management with antiplatelet therapy may be important.